Advances in electronic materials for clean energy conversion and storage applications - Khan, Aftab Aslam Parwaz; Nazim, Mohammed; Asiri, Abdullah M. (Woodhead Publishing, 2023)
Advances in Electronic Materials for Clean Energy Conversion and Storage Applications reviews green synthesis and fabrication techniques of various electronic materials and their derivatives for applications in photovoltaics. The book investigates recent advances, progress and issues of photovoltaic-based research, including organic, hybrid, dye-sensitized, polymer, and quantum dot-based solar cells. There is a focus on applications for clean energy and storage in the book. Clean energy is defined as energy derived from renewable resources or zero-emission sources and natural processes that are regenerative and sustainable resources such as biomass, geothermal energy, hydropower, solar and wind energy. Materials discussed include nanomaterials, nanocomposites, polymers, and polymer-composites. Advances in clean energy conversion and energy storage devices are also reviewed thoroughly based on recent research and developments such as supercapacitors, batteries etc. Reliable methods to characterize and analyze these materials systems and devices are emphasized throughout the book. Important information on synthesis and analytical chemistry of these important systems are reviewed, but also material science methods to investigate optical properties of carbon-nanomaterials, metal oxide nanomaterials and their nanocomposites. Reviews the latest advances in electronic materials synthesis, fabrication and application in energy Discusses green, cost-effective, simple and large-scale production of electronic materials Includes critical materials and device characterization techniques that enhance our understanding of materials' properties and measure device performance.
Part I: Advanced electronic materials for solar energy applications 1. Introduction to advanced electronic materials for solar energy applications 2. Advanced electronic materials for engineering energy applications 3. Carbon-based nanomaterials for solar energy 4. Quantum dots/Nanoparticles for solar energy 5. Organic semiconducting materials for solar energy 6. Small molecule organic solar cells 7. Polymer Organic Solar Cells 8. Metal halide hybrid perovskite materials for solar energy 9. Metal-halide perovskite nanomaterials and applications 10. Metal-halide perovskites for hybrid solar cells 11. Photon-downconversion materials for solar energy 12. Quantum dot as photon-downconversion materials 13. Organic dyes as photon-downconversion materials 14. Polymer-based nanocomposite for solar energy applications 15. Prospects and future perspective of electronic materials for solar cell applications Part II. Advanced electronic materials for energy storage (supercapacitor and battery) applications 16. Introduction to advanced electronic materials for energy storage applications 17. Advanced electronic materials for engineering energy storage applications 18. Carbon-based nanomaterials for supercapacitor electrode materials 19. Transition metal oxide nanomaterials as electrodes for supercapacitor applications 20. Transition metal oxides as electrode materials 21. Graphene derivative/transition metal oxides nanocomposites as electrode materials 22. Polymers-based nanocomposite as electrode materials for supercapacitor applications 23. Transition metal oxide nanomaterials-based electrodes for battery applications 24. Carbon-based nanomaterials for battery applications 25. Graphene-derivative decorated transition-metal oxide nanocomposites for battery applications 26. Prospects and future perspective of nanomaterials for energy storage applications
Keywords: Clean energy.; Energy conversion.; Energy storage.; Electronics -- Materials.; elektronické knihy; electronic books